After rights, after Man? Sylvia Wynter, sociopoetic struggle and the 'undared shape' - Odysseos, Louiza (The international journal of human rights, 2024)
Decolonial and post-colonial critiques have shown how rights naturalise a normatively white, Western bourgeois, and appropriative subject, while negating other forms of being and subjectivity. Given the disquiet around rights and their subject, reimagining the subject of rights calls on us to think 'after rights?'. Thinking 'after rights?', and insisting on the question mark, I argue, entails seeking the 'undared shape' (Aimé Césaire) of rights untethered from the figure of sovereign Man. Sylvia Wynter's historical-philosophical critique of Man, and search for the human 'after Man', are central for understanding the colonial-modern order and the role of rights within this. Extending Wynter's orientations, I first analyse how rights are implicated in modernity-coloniality's material and symbolic violences. Second, I examine Wynter's amplification of sociopoetic struggles - those wide-ranging modes of sociality and cultural, survival practices - by Man's enslaved and colonised Others. Such struggles aimed to displace Man as locus of colonial-modern structures, forging new meanings and modes of world-making untethered from this hegemonic figure. Importantly for rights and world politics scholarship, sociopoetic struggles work with abolitionist-reparative intent towards modernity-coloniality and its master subject. Finally, I consider what renarrating the human outside Man's horizon - as abnormative, insovereign and anti-individualist praxis - means for human rights.